The pregnant pause: exploring expectations and experiences of pregnancy and motherhood in a Cape Town body positive community - Le Roux, Jodi (Social Anthropology, 2021)
This dissertation explores the concepts of pregnancy and motherhood held by women in body positive communities in Cape Town, South Africa. By focusing on their expectations and experiences of these concepts within body positive communities and their wider social circles, the research examines what it means for women to want or not to want to be pregnant; what it means to be pregnant; whether pregnancy and motherhood are experienced as sociallyascribed performance, and what it might look like to challenge the social conventions around pregnancy and motherhood. The contextual landscape where the perception of women is typically polarized into contradictory identities through pro-natal social convention, frames the research. I collected data over a six month period through multi-sited ethnography and the qualitative anthropological techniques of participant observation, semi-structured interviews and autoethnography. Through an overarching lens of intersectional feminism I drew from an interdisciplinary body of literature, focusing on body positivity, embodiment, gender identity roles, sexuality and resistance, to consider each woman's lived experiences and the ways in which they inhabit or don't inhabit the conflicting identities that society impresses upon them. The research revealed a number of themes: Firstly, within these communities, the exploration of body positivity is inextricably fused with the project of reclaiming female sexuality. Secondly, expectations and experiences of pregnancy and motherhood revealed tensions and paradoxes between the expectation of the ‘ordentlike', natural mother as a social object and the individual subjective self and her rights and desires. Thirdly, body positive communities enable members to enact both overt and tacit forms of resistance in opposition to South African gender norms and roles. The research demonstrates that, body positive communities provide safe spaces and support for these women in terms of personal expression, growth and healing.